Anthrax: Distribution, Knowledge, Attitude and Practice Towards Pastoralists in Jawhar, Qalimow and Adan Yabal Somalia. - Abdirahman Barre; Abdihamid Salad Hassan; Abdullahi Nur Mohamed (Journal of Applied Veterinary Science And Technology, 2024)
Anthrax is a Zoonotic Disease (both Human and Animals) the disease is causing higher morbidity and mortality rate in Middle-Shebelle Somalia. Anthrax is a rare infectious disease caused by the bacterium Bacillus anthraces. It was reported in many parts of the region the disease is endemic that effects production with the pastoralists with an incidence >30% of their livestock production system. In a study to determine the status of anthrax in pastoralists in three selected area of Middle-Shebelle: Jawhar, Qalimow, and Aaden yabaal with Forty two herds were also used. The three selected area of the study were the most livestock populations in Middle-Shebelle. A structured Questionnaire was used to capture pastoralists Knowledge, Attitude and Their Practice with regards of Anthrax Disease. A cross-sectional survey was conducted contemporaneously with focus group discussions (FGDs) and key Informant interviews (KIIs) between May 2020 and April 2021. A Four Hundreds (4OO) of Households were visited via Personal interview. The existence of the disease per herd were estimated that 18.1% of camel herds, 34.3% of cattle herds and 47.6% of small ruminants flocks. Thus the summary of the KAP Results indicated that there was lack of Knowledge and Practice Gap among pastoralists related anthrax Disease. Generally, majority of farmers were practicing poorly in livestock community that was created the distribution of the disease. Therefore, the cattle sheep and goat herds should aware the diseases about the characterization and controlling systems through extending and trading for pastoralists and households. In addition, further assessment and control coverage with anthrax disease will highly option of essentials.